PERAN ASPEK KOMUNIKASI PADA PROGRAM CORPORATE VOLUNTEERING TERHADAP CITRA PERUSAHAAN DAN LOYALITAS - Arum, Maliana Puspa; Susanto, Irwan (E-Jurnal Manajemen, 2022)
This study aims to analyze the role of communication aspect in corporate volunteering program to company image and customer loyalty. The number of respondents’ data were 120 samples at bank BTPN Purwokerto. Analytical tool of this research is model of structural equation (Structural Equation Modeling) by utilizing program AMOS 16.0. The research result proves that the communication aspect has a role as the trigger of the customer's familiarity towards the corporate volunteering program and can create positive image of the customer as well as create customer loyalty of BTPN bank. Keywords :Aspects of communication; familiarity; corporate image; and customer loyalty